The need for eye protection during general anaesthesia and the efficacy of various eye protection methods - George, Twinkle Ann; Abraham, Biju; George, Nikhil (International Journal of Research in Medical Sciences, 2017)
Background: Patients undergoing prolonged non-ocular surgery with general anaesthesia may develop ocular complications. Previous studies suggested that prophylactic ocular care should include prevention of mechanical exposure of cornea and replacement of deficient tears. Methods: To assess the basal tear volume with various eye protection methods during general anaesthesia so as to find the need of eye protection and also to compare and assess the efficacy of lid taping with hypo allergenic adhesive surgical paper tape, paraffin based lubricant eye ointment, 2% hydroxyl propyl methyl cellulose tear substitute ointment and combinations of these ointments with lid taping as eye protection methods during general anaesthesia, the study was conducted in a tertiary care centre during the period of 1 year among 200 patients (400 eyes) undergoing general anaesthesia. After obtaining written informed consent they were subdivided into four groups of fifty patients each by randomization. A multiple cross over design with four groups each divided into two sub groups for eye protection methods was done. Corneal staining by fluorescein and basal tear volume assessment by Schirmer’s test were done pre-and postoperatively. Significance is assessed at 5 % level of significance. Student t test (two tailed, dependent) has been used to find the significance of study parameters (schirmer’s test score) on continuous scale within each group. Results: The percentage of difference of schirmer’s test score pre-and post-operatively were almost the same in all methods. Conclusions: Eye protection is mandatory in all cases under general anaesthesia. There was almost equal effectiveness for all eye protection methods analysed.